Effect of Cation Demixing on the Electrochemical Performance of LSCFO Cathodes for SOFCs - Baque, Laura Cecilia (2014)
The commercialization of Solid oxide fuel cells (SOFCs) is still hindered by their cost and long term degradation. One of the most common degradation mechanisms of La1-xSrxFe1-yCoyO3-d (LSCFO) cathodes reported in literature is element demixing. In this work, the degradation of LSCFO cathodes deposited on Ce1-xGdxO2-d electrolytes at 800°C in air for 50 h was investigated by electrochemical impedance spectroscopy (EIS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). EIS spectra from LSCFO cathodes present two contributions: one at high frequency and another at low frequency. The high frequency contribution remains invariable during the ageing treatment while the low frequency contribution continuously increases. The formation of small segregates was observed after the ageing treatment. Energy dispersive spectroscopy analysis reveals that these segregates were particularly poor in Sr.